1990/91ネン カキ,キングジョージ トウ チョウジョウ キチ ニ オケル ニッチュウ キョウドウ カンソク ダイ 3 ネンジ - 大谷, 修司; オオタニ, シュウジ; 中坪, 孝之; ナカツボ, タカユキ; Ohtani, Shuji; Nakatsubo, Takayuki (1992)
P(論文) 昭和63年度から3年計画で日中共同観測, 「大陸性南極と海洋性南極における動植物相の比較研究」が進められてきた。その第3年次として, 第7次中国南極考察隊に参加した。キングジョージ島の長城基地に1990年11月から1991年2月まで滞在し, 淡水藻類と蘚苔類を対象として調査研究を行った。野外調査は主にファイルズ半島(Fildes Peninsula)で行い, 淡水藻類に関してはこれまでに約110種類を識別した。氷雪藻類については, その分布を立地条件や雪の性状と関連させ, 中国生物担当隊員と共同で調査を行った。蘚苔類については蘚類の光合成, 呼吸活性を経時的に測定し, 同時に群落の微気象観測を実施した。また, 複数の種よりなる蘚類コロニーの構造と動態を調べるため, それらの縦断切片を作製し観察した。 The collaboration between Japanese and Chinese biologists started in the 1988/89 season with a three-year program at Great Wall Station, King George Island. For the third year of the program (1990/91), two Japanese botanists carried out the field survey on freshwater algae and bryophytes in the 7th Chinese National Antarctic Expedition (CHINARE-7). Taxonomic study of freshwater algae was carried out at the Fildes Peninsula. About 110 taxa were recognized in the samples collected from a variety of freshwater habitats. Distribution of snow algae was studied with reference to microhabitat and snow properties as a co-operative study with a Chinese scientist. The microclimate and photosynthetic activities of moss colonies around Great Wall Station were studied. Vertical cross-sections of moss colonies were examined to study the structure and dynamics of moss colonies. departmental bulletin paper